The Effect of Sharia Financial Literacy On Msme Growth: Competitive Advantage As A Mediator Among Muslim Entrepreneurs - Chandra Satria; Erna Maulina; Margo Purnomo; Tulus Suryanto (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2026)
The purpose of this research is to identify and measure the level of Islamic financial literacy and other related variables influencing the growth of MSMEs in Palembang Jaya Market, Palembang, South Sumatra, Indonesia. This study focuses on examining the effect of Islamic financial literacy and additional variables on MSME development. It explains the extent to which small and medium enterprises in Palembang understand and implement Islamic financial literacy, both directly and indirectly, through the mediating variable of Competitive Advantage of Muslim Entrepreneurs, in supporting the growth of MSMEs at Palembang Jaya Market. The research sample consisted of 373 MSME actors and related stakeholders selected from a total population of 5,512 business units operating in Palembang Jaya Market. A survey method was employed to measure Islamic financial literacy and intervening variables, including the Competitive Advantage of Muslim Entrepreneurs. Data were collected through a quantitative survey approach and analyzed using the SEM Statistical Test Application Version 4. The findings confirm a significant relationship between Shariah financial literacy and the Competitive Advantage of Muslim Entrepreneurs in influencing MSME growth at Palembang Jaya Market. Furthermore, Islamic financial literacy affects MSME growth both directly and indirectly through the mediation of Competitive Advantage, consistent with the Knowledge-Based View (KBV) theory. These results offer practical implications by providing policy makers with strategic insights to enhance MSME growth in Palembang Jaya Market through strengthening Shariah financial literacy supported by the competitive advantage of Muslim entrepreneurs.